2014
DOI: 10.1002/ece3.553
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite and Wolbachia analysis in Rhagoletis cerasi natural populations: population structuring and multiple infections

Abstract: Rhagoletis cerasi (Diptera: Tephritidae) is a major pest of sweet and sour cherries in Europe and parts of Asia. Despite its economic significance, there is a lack of studies on the genetic structure of R. cerasi populations. Elucidating the genetic structure of insects of economic importance is crucial for developing phenological-predictive models and environmental friendly control methods. All natural populations of R. cerasi have been found to harbor the endosymbiont Wolbachia pipientis, which widely affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 94 publications
(182 reference statements)
1
25
0
1
Order By: Relevance
“…To separate environmental from genetic factors contributing to the potential variation in diapause intensity among the three populations, their genetic structure should be considered. Using microsatellite markers, it has recently been revealed that the two Greek populations used in our study form one cluster with moderate levels of gene flow, whereas the German population is quite different from the previous cluster (Augustinos et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To separate environmental from genetic factors contributing to the potential variation in diapause intensity among the three populations, their genetic structure should be considered. Using microsatellite markers, it has recently been revealed that the two Greek populations used in our study form one cluster with moderate levels of gene flow, whereas the German population is quite different from the previous cluster (Augustinos et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…We expect that pupae from warm regions need a shorter exposure to cold for terminating diapause than those from cold ones. In an attempt to distinguish between genetic and environmental effects on diapause intensity, we selected populations with different gene flow rates (Augustinos et al, 2013). Specifically, we used pupae from two Greek populations (Kala Nera and Dafni) with moderate gene flow rates and one German population (Dossenheim) genetically different from the Greek ones.…”
Section: Introductionmentioning
confidence: 99%
“…Although screening is far from complete, well-established infections have been found in some species. The best characterized species is Rhagoletis cerasi , since all natural populations studied so far are 100% infected, usually with multiple-strain infections (Riegler and Stauffer 2002, Kounatidis et al 2008, Arthofer et al 2009, Augustinos et al 2014a, Karimi and Darsouei 2014). More importantly, it is a well-documented example of the implication of Wolbachia in restriction in gene flow and enhancement of incompatibility between natural populations of the species (Riegler and Stauffer 2002).…”
Section: Introductionmentioning
confidence: 99%
“…, 2013), or by contact of haemolymph through wounds in the host's bodies (Rigaud and Juchault, 1995). Horizontal transmission was also considered the route of infection by multiple Wolbachia strains, as is frequently observed in many species of Coleoptera, Diptera, Hymenoptera and Lepidoptera (Werren et al , 1995; Jamnongluk et al , 2002; Rokas et al , 2002; Reuter and Keller, 2003; Hiroki et al , 2004; Schuler et al , 2011; Yang et al , 2012, 2013; Augustinos et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Among the frugivorous tephritid flies, Wolbachia was found to infect species of the genera Rhagoletis (Riegler and Stauffer, 2002; Schuler et al , 2009, 2011, 2013; Arthofer et al , 2009; Drosopoulou et al , 2011; Augustinos et al , 2014), Bactrocera (Kittayapong et al , 2000; Jamnongluk et al , 2002; Liu et al , 2006; Sun et al , 2007; Morrow et al , 2014, 2015), Dacus (Kittayapong et al , 2000), Ceratitis (Rocha et al. , 2005), and Anastrepha (Werren et al , 1995; Selivon et al , 2002; Coscrato, et al , 2009; CĂĄceres et al , 2009; Marcon et al , 2011; MartĂ­nez et al , 2012).…”
Section: Introductionmentioning
confidence: 99%